Labor Nature of Delivery Contracts and Computer Applications - Porras Velasco, Angélica (2023)
This work is the result of an investigation carried out about the doctrine and jurisprudence regarding labour nature of contracts between the “riders” and the digital delivery platforms. Although it is true, these contracts have a civil or commercial form, we think they are true labour contracts. Determination of labour contract features are conflicting and required the reformulation of classic concepts of Labor Law such as: dependency or alienation, in order to adapt them to the changes introduced by technology and the internet in the world of work. Although, this investigation is focused in Ecuador case, we have analized Spanish case, because in Spain, through a long judicial battle, many juriprudential rulings have established that delivery platform workers are dependent, not self-employed, and therefore, the Labour Law are applied to them. In our country there is a different development in this issue, the debate has not even reached academic legal forums, let alone the courts and other institutions, despite the fact that several legal projects are been analized at the National Assambly and the workers are demanding their recognition as such.